(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The method of sealing materials effectiveness evaluation in the repair of bituminous-concrete surface with transversal cracks is offered. Calculation schemes and mathematical models based on the application of the thermo-viscous-elasticity theory for the prediction of temperature stresses in the sealing material at the contact with the bituminous-concrete surface, taking into account the thermal-technical and thermorheological properties of the materials and the geometric parameters of the bituminous-concrete slabs and the transversal crack. The obtained analytical dependences allow to estimate the service life before the loss of sealant compound integrity or adhesive strength of their adhesion with bituminous-concrete surface taking into account annual and daily temperature fluctuations according to the main provisions of the kinetic theory of solid bodies strength.